Answer:
![g(x)=(x)/(4) -3](https://img.qammunity.org/2019/formulas/mathematics/middle-school/m4phh46xekyjxmvsm4elpqqt0aqzazdezu.png)
Explanation:
Ve have the function:
![f(x)=y=4x+12](https://img.qammunity.org/2019/formulas/mathematics/middle-school/w633gzgncy2r6ttf1mmr51lua72ppmq9kq.png)
The first step to find the inverse is to exchange the variables, that is where we see
put
and where we see
put
:
![x=4y+12](https://img.qammunity.org/2019/formulas/mathematics/middle-school/zy52kj62zys1l1qnes9m0uktw11ttfxzau.png)
And we clear for the variable
:
![x-12=4y\\(x-12)/(4) =y\\(x)/(4) -3=y](https://img.qammunity.org/2019/formulas/mathematics/middle-school/rejoue87njhvg4y55b9uyus3edpzh554vj.png)
This would be the inverse of the function (since we know that
), and according to the problem the inverse of
is
, so:
![g(x)=(x)/(4) -3](https://img.qammunity.org/2019/formulas/mathematics/middle-school/m4phh46xekyjxmvsm4elpqqt0aqzazdezu.png)